The Rise of Effective States in Europe. (27th August 2015) - Dincecco, Mark
Abstract : This review article examines the development of state capacity—the extractive and productive power of states— in European history. To explain the historical evolution of state capacity, I focus on the role of political innovations. I relate state capacity improvements to long-run economic growth and the establishment of twentieth-century welfare states. The article concludes with historical lessons for developing nations today."In framing a government which is to be administered by men over men, the great difficulty lies in this: you must first enable the government to control the governed; and in the next place oblige it to control itself." James Madison (1788, p. 257)